3D integration of pH-cleavable drug-hydrogel conjugates on magnetically driven smart microtransporters. (1st January 2021) - Bernasconi, Roberto; Mauri, Emanuele; Rossetti, Arianna; Rimondo, Stefano; Suriano, Raffaella; Levi, Marinella; Sacchetti, Alessandro; Pané, Salvador; Magagnin, Luca; Rossi, Filippo
Abstract: Targeted drug delivery is currently emerging as a promising approach to overcome the limits of currently employed administration techniques. The most convenient methodology to control drug delivery is the application of stimuli-responsive materials, which can release drugs only when required, to remotely controlled microdevices able to navigate human body. Thanks to this synergy, release can be controlled both spatially and temporally. Spatial control is guaranteed by the maneuverability of the devices, which can be precisely guided to release in targeted locations. Temporal control, conversely, is guaranteed by the functionalization introduced in the stimuli-responsive material. In this context, the present work describes the coating of magnetically controlled microdevices with functionalized alginate-based hydrogels able to release drugs at pH values lower than 4.5. Hydrogels are functionalized binding the drug with either an azidoethyl ester bond or an amidic bond, following an innovative synthesis route. After fabrication, release from hydrogel coated microdevices as a function of the environmental pH is characterized. Finally, devices are magnetically actuated and the possibility to achieve spatially and temporally controlled release is demonstrated. The functional microtransporters described in the present work are particularly promising for in-vivo applications in environments where pH differences are present, like the digestive apparatus. Graphical abstract: Unlabelled Image Highlights: Functionalized alginate hydrogels for pH controlled drug release are synthesized. Functionalization is designed to allow sustained drug release only at pH lower than 4.5. Hydrogels are applied on magnetically steerable devices able to navigate human body. Hydrogel coating onto microrobots create drug carriers that can reach specific target sites. Hydrogel coating functionalization can guarantee the release of drugs only in the target site.